SKALA KOMA GLASGOW AWAL SEBAGAI PREDIKTOR NYERI KEPALA KRONIK PASCATRAUMA KEPALA NON BEDAH - Desie Yuliani, I Made Oka Adnyana, Thomas Eko Purwata, Eka Widyadharma (NEURONA, 2013)
INTRODUCTION TRAUMATIC BRAIN INJURY IS A SIGNIFICANT PUBLIC HEALTH PROBLEM CONVENTIONAL STAGING OF TRAUMATIC BRAIN INJURY TYPICALLY USES GLASGOW COMA SCALE GCS TO ASSES DEPTH OF COMA AS A SEVERITY MARKER HEADACHE IS THE MOST COMMON SYMPTOM OF POST TRAUMATIC SYNDROME